Public health strategies to combat measles outbreaks in low-vaccination areas - Alsharif, Sultan M.; Noorelahi, Amroo K.; Althagafi, Thamer M.; Alsayel, Lama T.; Alfaraj, Lena H.; Alshamase, Raqhda B.; Hejji, Ammar A.; Alzhrani, Samia A.; Arishi, Rayed Y.; Alsuaileek, Nainawa A.; Alfadl, Danya W.; Abdulkarim, Hanadi A. (International Journal Of Community Medicine And Public Health, 2024)
Measles outbreaks are particularly common in regions where vaccination coverage falls below the required thresholds for herd immunity. These outbreaks often result in high morbidity and mortality rates, especially among children. This review examines public health strategies to combat measles outbreaks, focusing on areas with suboptimal vaccination coverage. Public health strategies to combat measles outbreaks in low-vaccination areas include mass vaccination campaigns, community engagement, enhanced surveillance, and strengthening healthcare systems. Vaccination campaigns are highly effective, but challenges like vaccine hesitancy and logistical barriers need to be addressed. Surveillance and healthcare system strengthening are essential for timely outbreak detection and effective management, despite limitations in resources​. The review also explores the barriers to vaccination, such as vaccine hesitancy, logistical issues, and socioeconomic factors, which contribute to low vaccination rates. Key strategies such as catch-up immunization programs, the use of social media to counter misinformation, and strengthening healthcare systems to support vaccination efforts are discussed. The review underscores the importance of comprehensive, multi-level interventions involving local communities, healthcare providers, and governments to prevent and control measles outbreaks. Recommendations for improving vaccination rates and outbreak preparedness in low-vaccination areas are also presented.